Determinants of long‐term outcome in severe alcoholic hepatitis. Issue 6 (23rd July 2013) - Potts, J. R.; Goubet, S.; Heneghan, M. A.; Verma, S.
Summary Background Although short‐term outcome in severe alcoholic hepatitis (SAH) is well described, its long‐term course remains uncharacterised. Aim To assess determinants of long‐term outcome in SAH. Methods Data were recorded from a cohort with SAH (admission Discriminant Function (DF) ≥32). Kaplan–Meier (KM) and Cox proportional hazards survival analyses were performed to determine predictors of outcome. Results One hundred and nine patients were included; 63.3% male, aged 49.6 ± 9.4 years with median follow‐up of 40.7 months (95% CI 37.2–44.3). Median DF was 58, 86.2% had cirrhosis and 65.1% received corticosteroids and/or pentoxifylline. Overall mortality was 57.8%, 96.8% of deaths being liver‐related and 65.1% occurring after the index hospitalisation. Estimated 5‐year survival was 31.8%. Hepatorenal syndrome was the only baseline factor independently associated with mortality (HR 3.78, 95% CI 1.98–7.19, P < 0.0001), although it predicted short‐term, rather than long‐term outcome (median survival 0.52 months, 95% CI 0.43–0.61). Of the 87 patients (79.8%) who survived index hospitalisation, 65.1% experienced recidivism. Abstinence at last follow‐up remained the only independent predictor of survival in multivariate analysis (HR 0.370, 95% CI 0.168–0.818, P = 0.014). Five‐year survival was higher in abstainers (75.3%) compared with relapsed and continued drinkers (26.8% and 21.0%, respectively, P = 0.005). However, the survival benefit from abstinence only became statistically significant at 18 months postdischarge (HR 2.714, 95% CI 0.995–7.404, P = 0.051). Conclusions Estimated 5‐year survival after index hospitalisation with SAH is 31.8% with alcohol relapse occurring in two‐thirds of patients. Abstinence remains the only independent predictor of long‐term survival. Novel strategies to improve abstinence after admission with SAH are urgently needed.